Evaluation of Supplemental Energy Source for Grazing Stocker Cattle - L. W. Lomas; J. K. Farney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
Thirty-six steers grazing smooth bromegrass pastures were used to evaluate the effects of a supplemental energy source on available forage, grazing gains, subsequent finishing gains, and carcass characteristics. Supplementation treatments evaluated were: no supplement, a supplement with starch as the primary source of energy, and a supplement with fat as the primary source of energy. Supplements were formulated to provide the same quantity of protein and energy per head daily. Supplementation with the starchbased or fat-based supplement during the grazing phase resulted in higher (P<0.05) grazing gains than feeding no supplement. Supplementation during the grazing phase had no effect (P>0.05) on finishing gain, feed intake, and feed:gain. Steers supplemented with the starch-based supplement had greater (P<0.05) final finishing live weight and greater (P<0.05) hot carcass weight than those that received no supplement.
Keywords: grazing; supplementation; energy; finishing